Integrasi Nilai-Nilai Kearifan Lokal Joka’ju Masyarakat Nggela dalam Membangun Karakter Sadar Bencana Siswa di Sekolah Menengah Atas - Sunimbar, Sunimbar; Mari, Natalia Adel H. N. (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2020)
Nggela Village, which is in the administrative area of Ende Regency, is one of the villages in the Wolojita sub-district which is prone to geological disasters, namely landslides. Mitigation efforts to increase public awareness in dealing with disasters can be done through education to students in Nggela village. Education is a conscious human effort in understanding themselves and their environment, or human efforts in understanding the interactions between the macro and micro cosmos. This research is focused as an effort to obtain an explanation of the integration of the values of local wisdom of the Nggela village community in the traditional Joka’Juceremony as a character formation of students in building disaster awareness behavior among students. The type of research is qualitative research particularly literature study with a descriptive analysis approach to produce information in the form of notes and descriptive data found in reference sources or literature. The traditional Joka’Juceremony which is carried out once a year to commemorate the new year according to local customs with the aim of repelling the bala or what is known as driving out evil spirits and as an effort to ask God to avoid disaster. This ceremony is a tradition and culture of the Indonesian people, especially the people on the Flores island, Ende Regency, Nggela Village, Lio tribe. This ritual is seen as one of the correct ones that was stated by its previous predecessors. This social value can be integrated as a disaster awareness effort for students in Nggela village where schools are obliged to equip students with education both theoretically (related to science and technology) and non-theoretically (relating to the formation of morals and character).